Nanoscale dual-gate InAlAs/InGaAs HEMT with improved characteristics. Issue 2 (2nd April 2020) - Mohapatra, M.; Panda, A. K.
ABSTRACT: This paper deals with the DC and Radio Frequency (RF) characteristics of InAlAs/InGaAs-based dual-gate high-electron-mobility transistor (DG-HEMT) for a 50 nm gate length. In single-gate HEMT (SG-HEMT), the gate length having less than 100 nm shows poor transconductance ( g m ) which reduces the voltage gain ( A v ) and maximum oscillation frequency ( f max ). To overcome this problem, a dual-gate structure is designed keeping the device dimensions unchanged and a numerical model is developed to study the effect of the dual gate. A comparative study of SG-HEMT and DG-HEMT is presented. For a DG-HEMT, a maximum drain current ( Ids ) of 310 mA/mm at Vds = 0.1 V, a peak transconductance ( g m _max ) of 2294 mS/mm, a cut-off frequency ( fT ) of 100 GHz and a maximum oscillation frequency ( f max ) of 270 GHz have been achieved. For reduced gate length, the DG-HEMT performs better due to the presence of dual gate and double heterojunction.